Strategi Penetapan Harga Jual dan Perencanaan Laba pada Bisnis Rintisan Haminjon - Sihaloho, Erik Morales; Odang, Nilam Kemala (Universitas Islam Islam Sumatera Utara, 2023)
Haminjon is a startup operating in the fragrance industry which is currently in the validation process and is being tested in the market. Haminjon produces diffusers made from Toba incense based on customer orders. This research aims to design pricing strategy and profit planning. The research method used is a qualitative method with a case study approach. The results of this research show that the existing selling price calculation results are appropriate and do not need to be changed to remain competitive in the market. However, production quantities need to be increased to the recommended range to reduce costs and obtain the expected profits. This will affect Haminjon's profit planning. Therefore, Haminjon should increase the production range so that the cost of production can be reduced. By utilizing the nature of cost behavior, affordable selling prices can be maintained and produce optimal profits.